Penerapan PENERAPAN METODE STRUKTURAL ANALITIK SINTETIK BERBANTUAN MEDIA GAMBAR SEBAGAI UPAYA MENINGKATKAN KETERAMPILAN MEMBACA PERMULAAN SISWA SEKOLAH DASAR - Yunsacitra; Ahmad Hariandi; Muhammad Sholeh (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
This research aims to describe the improvement of beginning reading skills through the application of the Synthetic Analytical Structural (SAS) method in grade 1 elementary school students. This research wa carried out at SDN 207/IV Jerambah Bolong, South Jambi sub-district, Jambi city, Jambi province. The form of this research is Classroom Action Research (CAR) using a qualitative approach. This research data was obtained by observation. Interviews, documentation, and tests. This research was carried out in 2 meetings. Each cycle consistsof four stages, namely planning, implementation, observation, and reflection. The results of this reserach were that there was an increase in intial reading skills in grade 1 students at SDN 207/IV Jerambah Bolong after applying the Synthetic Analytical Structural (SAS) method at each meeting in each cycle.